Researching boxing bodies in Scotland: Using apprenticeship to study the embodied construction of gender in hyper masculine space. Issue 7 (3rd July 2017) - Carlsson, Hanna
Abstract: This article presents apprenticeship as an ethnographic method suitable for researching topics concerning gender and space. To use this method, the researcher takes up a practice, such as a sport. Emphasis lies in understanding one's topic 'by body', and the article argues that such an embodied perspective sheds a new light on gender construction in the boxing gym. An empirical study of female amateur boxers in Scotland, conducted by the author, herself a competitive female boxer, reinforces the argument. The position of an embodied insider offers the researcher a unique vantage point with regard to various contrasting processes of gender construction on different scales, such as the body, embodied encounters and the gym. By giving attention to the transformative power of bodily practice, apprenticeship focuses on possibilities for, resistance to, and transformation of, gender norms in hyper masculine spaces. The apprenticeship method can therefore enrich geography's understanding of the role of physical practices for gender construction in different spaces.